Role of Carboxylesterases in Xenobiotic Metabolism and Detoxification: Insights for Cheminformatics Approaches - Sakshi Chaudhary; Neetu Saharan (International Journal of Cheminformatics, 2025)
Xenobiotics, which include a wide range of environmental pollutants, food additives, drugs, and carcinogens, are foreign chemical entities that enter the human body and may accumulate, leading to toxic effects. Phase I and phase II metabolic responses are among the detoxification procedures that are necessary to lessen these negative consequences. This review highlights the pivotal role of carboxylesterases (CES), enzymes involved in the hydrolysis of ester, amide, and thioester bonds in xenobiotics, in the metabolism and detoxification of these substances. We discuss the structural and functional properties of CES, their tissue distribution, and the implications of their activity in drug metabolism and environmental toxin clearance. In the context of cheminformatics, we explore how computational models can assist in predicting CES activity, understanding substrate specificity, and designing drug molecules or inhibitors that modulate CES activity. The information presented here provides valuable insights for both pharmacological applications and environmental health assessments.
Keywords: Carboxylesterases; Cheminformatics; Enzyme Modulation; Phase I and II Metabolism; detoxification; drug metabolism; xenobiotics